Application Of Personal Hygiene In The Production Process At The Salsabila Gift Shop - Darmadi, Nadia Mastura; Yulastri, Asmar; Fridayati, Lucy; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Hygiene in the production process certainly determines product results, especially production in the food sector. Based on the results of studies at the Salsabila Souvenir Shop, it shows that one of the principles of food sanitation hygiene according to the Indonesian Ministry of Health has not been fulfilled, namely in food processing. In product processing, employees at the Salsabila Souvenir Shop have not paid attention to the requirements set by the Ministry of Health, namely personal hygiene. This research aims to find out how employee personal hygiene at the Salsabila Souvenir Shop is implemented in the production process, so that employees can understand the correct standards in handling personal hygiene so as not to contaminate production results. Employee self-awareness in the field of cleanliness is very necessary to ensure production quality that must be able to satisfy customers. This research becomes a reference material for employee introspection regarding standards for creating a clean work environment. This type of research is descriptive research with a quantitative approach. The subjects of this research were all 15 employees at the Salsabila souvenir shop. The sampling technique uses a saturated sampling technique so that the entire population becomes the sample. The data collection technique was carried out using a questionnaire with a Likert scale whose validity and reliability have been tested. Next, the data was analyzed through descriptive analysis using the assessment categorization method.Based on the research results, it shows that the results of research conducted on the personal hygiene application variable from 15 respondents can be explained that the level of achievement of respondents in the application of personal hygiene in the production process at the Salsabila souvenir shop was obtained at 41% in the low category.Based on the data obtained and analysis of field data, it can be concluded that the Implementation of Personal Hygiene in the Production Process at the Salsabila Souvenir Shop is still in the low category, this is due to the fact that there are employees who do not fully comply with the specified operational standards, such as not wearing work clothes, aprons, and gloves when working, causing the work to be ineffective and the food to become contaminated by bacteria.